The invention of the athletic body - Hortensia Moreno (Antropólogos Iberoamericanos en Red, 2013)
Based on two mythic figures − one belonging to classic Greece (the “Glowing Body”), and another to primitive Christianity (the “Heavenly Body”) − I reflect on the symbolic logic of exclusion as enacted in four moments in the history of the Olympic Games. The first has to do with the invention of amateurism in the sporting philosophy of Coubertin, or the class exclusion. The second refers to the Anthropology Days held at the 1904 Olympic Games in Saint Louis (Missouri), or the ethnic/racial exclusion. The third is the Berlin Parade of Nations in 1936, or the national supremacy. The fourth explores the introduction of gender verification in Mexico City (1968), or the gender exclusion. In this fashion, we re-connect the imagined/imaginary configuration of the body with practices and politics which will result in an anthropological rationalization of discrimination.